IMPACT OF BRAZILIAN PUBLIC POLICIES AIMED AT THE INTEGRATION OF DIGITAL TECHNOLOGIES IN SCHOOLS (Editora Impacto Científico, 2025)
This study aims to present the results of an investigation into the impacts of Brazilian public policies aimed at the inclusion of digital technologies in schools. A total of 17 teachers participated in the analysis, five from a private institution and 12 from a public state school in Piracanjuba, Goiás. The research has a qualitative approach and uses the content analysis technique to interpret the responses obtained through the application of an online questionnaire consisting of five questions, among them: “What is digital technology for you?”, “Do you feel prepared to use digital technologies in your classes?”, “Do you consider that digital technologies contribute to student learning?” Among the impacts, it was identified that 41.17% of teachers claim to have theoretical knowledge about technologies, but do not have adequate training to integrate them efficiently in the classroom. The infrastructure of the school environment, professional devaluation, overcrowding in public schools, lack of equipment for all students and poor quality of the internet hinder the use of these technologies. In summary, the research indicates that despite the existence of several public educational policies, the insertion of technologies still does not reach all schools. Learning continues, most of the time through expository classes. As a methodology, the study was characterized by a bibliographic research whose authors described the theme with a qualitative approach in order to deepen knowledge on the subject.